Penerapan Ice Breaking untuk Meningkatkan Semangat Belajar Mengaji Santri Balita di TPQ Masyithoh Kabupaten Pasuruan - Mukarromah Mukarromah; Asep Rahmatullah (Filantropis: Jurnal Pengabdian kepada Masyarakat, 2025)
Al-Qur'an learning for toddlers at TPQ Masyithoh in Pasuruan Regency faces the challenge of low enthusiasm and focus in learning. This community service program aims to increase the enthusiasm of students through the application of ice breaking. The activity began with observation and problem identification through direct observation and interviews with female teachers to understand the classroom conditions and teaching obstacles. Based on these findings, the team designed an ice-breaking package consisting of Islamic cheers, religious songs, educational games, Islamic storytelling, and group prayers with movements. The program was then socialized and coordinated with the TPQ to ensure smooth implementation. Ice breaking activities were carried out regularly before lessons began, with direct assistance from the PKM team to the teachers. Evaluations were conducted periodically by observing changes in student behavior, interviewing teachers, and documenting the activity process. The results showed an increase in enthusiasm, participation, and attention among students in Al-Qur'an learning. Teachers also felt that it helped them in managing their classes. The activity was concluded with a reflection and the preparation of an “Ice Breaking for TPQ” report as a form of program sustainability. In conclusion, ice breaking proved to be an effective learning strategy that was enjoyable and applicable for increasing the learning motivation of preschool students, and has the potential to be replicated in other TPQs with similar conditions.